Brain rules ebook 12 principles for surviving and thriving at work, home, and school. - Medina, John (2010)
In Brain Rules , Dr. John Medina, a molecular biologist, shares his lifelong interest in how the brain sciences might influence the way we teach our children and the way we work. In each chapter, he describes a brain rulewhat scientists know for sure about how our brains workand then offers transformative ideas for our daily lives. Medina’s fascinating stories and infectious sense of humor breathe life into brain science. You’ll learn why Michael Jordan was no good at baseball. You’ll peer over a surgeon’s shoulder as he proves that most of us have a Jennifer Aniston neuron. You’ll meet a boy who has an amazing memory for music but can’t tie his own shoes. You will discover how:    * Every brain is wired differently     * Exercise improves cognition     * We are designed to never stop learning and exploring     * Memories are volatile     * Sleep is powerfully linked with the ability to learn     * Vision trumps all of the other senses     * Stress changes the way we learn In the end, you’ll understand how your brain really worksand how to get the most out of it.